Ethnoscience-Based Interactive E-Module: E-Module Development on Nonrenewable Resources Topic - Widayanti, Widayanti; Amaliah, Khusnatul; Sholikhah, Ainun Ummi; Kurniawan, Andrew (Indonesian Journal of Science and Mathematics Education, 2022)
This study aims to develop an ethnoscience-based interactive e-module with the topic of non-renewable resources. Research and Development in this study adopted the ADDIE theory by Dick and Carry which consists of five stages: 1) Analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. This research only reached the third stage because at that stage the research objectives had been achieved. The instrument of this research is a Likert scale questionnaire which is analyzed by percentage. The results showed that the interactive e-module was declared feasible to be applied in learning with content and media expert validators giving an average score of above 75%. Student responses to this e-module also reached more than 75%, so this interactive e-module was stated to be very interesting. The conclusion of this study is that this interactive e-module is valid so that it can be applied in physics learning. For further research, it is hoped to develop e-modules on different topics.